Speech by Prof. Paul Musili Wambua Chancellor, University of Embu During the 4th Graduation Ceremony - Wambua, Paul M. (University of Embu, 2019)
Speech by Prof. Paul Musili Wambua Chancellor, University of Embu During the 4th Graduation Ceremony at University of Embu on 14th September 2019 at 9.00 A.M.